Leading Sectors 15 Countries-District in Central Java - Daryono Soebagyo; Arifin Sri Hascaryo (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2016)
Sectors of the economy are vital to the economic growth of a region. A sector can be said to be high productivity levels and if the sector is able to absorb a large workforce and the use of human resources as efficiently as possible. Each area has advantages in certain sectors which could be a contributor to economic growth. This study was conducted to determine and explain the influence of the areas that have a particular advantage to economic growth. Measurements using the Location Quotient leading sectors, whereas the determinant analysis using panel data. This research is expected to know the areas that have the basic sector and determine its impact on economic growth in Central Java. An area is said to have a dominant sector if it has a score of more than 1 and is said not to have if less than 1. The sample used in this study are 15 city / county for the years from 2007 to 2011. The results of the analysis using the LQ shows that in 2007-2011 there were about eight areas that excel in the agricultural sector, 9 in the industrial and commercial sector.